Benefits of Drilling Repetition in Enhancing Second Language Learners’ Speaking Ability - Melania Mendrofa; Marchellina Wijaya (International Journal of English and Applied Linguistics (IJEAL), 2022)
This paper aims to analyze the significance of drilling repetition in enhancing second language learners' speaking ability. In learning a second language, some learners may overcome problems in saying words or sentences. In some cases, they also mispronounce the words. These can occur because of some problems, such as a lack of confidence, a lack of practice, and less feedback from the teacher. Based on this issue, this paper is concerned with the discussion of how the drilling technique can be a solution to the problem and its benefits to the students' speaking performance. This paper uses qualitative research analysis and a descriptive method to discuss the finding. The equipment that was implemented for this paper is journals and books. The benefits of drilling repetition are providing learners with intensive practice in hearing and saying particular word phrases. They can help with memorization and automation of common language patterns, providing the opportunity for learners to get immediate feedback, assisting learners in noticing the correct form or pronunciation of a word or phrase, which makes the learners speaking ability accurately, and building confidence. This paper finally points out that the benefits of adopting drilling repetition in enhancing second language learners' speaking ability are helpful to building learners' confidence and fluency in speaking the second language.